Histomorphology of surgically removed fallopian tubes - Sameera N Patel; Shreya A S; Sujata S Giriyan (International Journal of Health and Clinical Research, 2022)
Background: Fallopian tubes are common surgical specimen in pathology laboratory and there have been only few studies documenting the variable presentations of fallopian tube pathology, which prompted the present study. Material and Methods: A two year prospective study of specimens of fallopian tubes was done Formalin-fixed, paraffin-embedded tissue sections were stained with hematoxylin and Eosin. Results: Inflammatory lesions of tubes comprised maximum number of cases followed by ectopic pregnancies. No primary neoplastic lesion was found in the study. Serial sections of fallopian tubes and section from representative areas are essential for a pathologist so that the diagnosis of these pathological entities is not missed. Conclusion: Most of the fallopian tube lesions were identified incidentally. Knowledge of the general frequency of these variations in general surgical pathology practice can be valuable to pathologists.